Going against the grain: Unravelling the habitus of older farmers to help facilitate generational renewal in agriculture. Issue 3 (10th July 2021) - Conway, Shane Francis; McDonagh, John; Farrell, Maura; Kinsella, Anne
Abstract: Limited uptake of financial incentives, designed to confront global trends of an ageing farming population and low levels of land mobility, reveal resistance or at best ambivalence, amongst farmers towards altering existing farm management and ownership structures in later life. To uncover facets governing the mindset, disposition and practices of older farmers towards succession and retirement, this study draws on Bourdieu's notion of habitus. A multi‐method triangulation methodology is employed to obtain in‐depth understandings of the senior generation's deeply embedded views, and the changes they perceive will occur upon their engagement in the process. Findings reveal that the attitudes and behaviour required to 'step aside' and retire from farming not only 'go against the grain' of the older farmers' habitus, appearing to be instinctively 'wrong', they also appear incompatible with what is necessary to earn recognition as a 'good farmer'. The article concludes by recommending that a shift in thinking towards succession and retirement must be confronted at an earlier life stage in order to inculcate a new farming habitus. In doing this, long‐term resolutions through generating a regularised, accepted and well‐regarded practice of intergenerational farm transfer within the farming community would be promoted.